PERTANGGUNGJAWABAN POLRI TERHADAP PENYALAHGUNAAN SENJATA DALAM BERTUGAS - Yudiastuti, Novitasari; Nugroho, Widhi Cahyo Nugroho (Research Journal of Social Science and Economics, 2023)
Law enforcement is a government agency that controls those who commit violations, one of which is the police. The police are taken from a Greek word, namely politie, which means the entire city-state government, so it goes from that word that the police are used to refer to a part of the government. In Indonesia, the police are a government agency or institution whose job is to arrest people who disobey or violate laws and so on. Regarding the distribution of powers from the police, it was adjusted to the division that originated from the previous Japanese military era, so that after that a police reorganization was held in 1994. Law no. 2 of 2002 stipulates that the duties of the police are to maintain order, obey the law and uphold and maintain public order. Because the goal of a rule of law is to serve the interests of the people, the interests of the government and the people unite, and they fight together, in this case the police take their point of departure from the people, serving the people. . with the people for the people. That is, citizens enjoy various rights and opportunities in all matters relating to the administration of government institutions, including the police and their vehicles. The status, role and duties of the Polri have changed and developed from the beginning to the present. These changes or developments have a significant impact on law enforcement efforts. These changes include socio-cultural changes. Police culture also transforms the values, beliefs, rules, norms, behaviors, and customs that make up police culture, and are often a combination of formal justice and the actions of the police, as well as those in informal organizations.